A longitudinal study of fecal calprotectin and the development of inflammatory bowel disease in ankylosing spondylitis. Issue 1 (December 2017) - Klingberg, Eva; Strid, Hans; Ståhl, Arne; Deminger, Anna; Carlsten, Hans; Öhman, Lena; Forsblad-d'Elia, Helena
Abstract Background Patients with ankylosing spondylitis (AS) are at increased risk of developing inflammatory bowel disease (IBD). We aimed to determine the variation in fecal calprotectin in AS over 5 years in relation to disease activity and medication and also to study the incidence of and predictors for development of IBD. Methods Fecal calprotectin was assessed at baseline (n  = 204) and at 5-year follow-up (n  = 164). The patients answered questionnaires and underwent clinical evaluations. At baseline and at 5-year follow-up, ileocolonoscopy was performed in patients with fecal calprotectin ≥500 mg/kg and ≥200 mg/kg, respectively. The medical records were checked for diagnoses of IBD during the follow-up period. Results Fecal calprotectin >50 mg/kg was found in two-thirds of the patients at both study visits. In 80% of the patients, fecal calprotectin changed by <200 mg/kg between the two measuring points. Baseline fecal calprotectin was positively correlated with Ankylosing Spondylitis Disease Activity Score based on C-reactive protein, Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Functional Index, C-reactive protein, erythrocyte sedimentation rate, and fecal calprotectin at 5-year follow-up. The use of nonsteroidal anti-inflammatory drugs (NSAIDs) was associated with higher fecal calprotectin, and 3-week cessation of NSAIDs resulted in a drop of a median 116 mg/kg in fecal calprotectin. The use of tumor necrosis factor (TNF) blockers was associated with lower fecal calprotectin at both visits, but the users of TNF receptor fusion proteins had significantly higher fecal calprotectin than users of anti-TNF antibodies at 5-year follow-up. The 5-year incidence of Crohn's disease (CD) was 1.5% and was predicted by high fecal calprotectin. Conclusions Fecal calprotectin was elevated in a majority of the patients and was associated with disease activity and medication at both visits. CD developed in 1.5% of the patients with AS, and a high fecal calprotectin was the main predictor thereof. The results support a link between inflammation in the gut and the musculoskeletal system in AS. We propose that fecal calprotectin may be a potential biomarker to identify patients with AS at risk of developing IBD. Trial registration ClinicalTrials.gov identifier:NCT00858819 . Registered 9 March 2009. Last updated 28 May 2015.